The Concept of Death in Emily Dickinson's 'I Cannot Stop for Death' - Thohiriyah Thohiriyah (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2017)
Through her poem, Emily Dickinson utilized figurative speech to elucidate the concept of death. In addition, the employment of the figurative speech is to illustrate what happened in the United States in the era of Puritanism. By using the concept of semiotics theory, the analysis shows that the poem demonstrates the passive protest over the organized religion that is being promoted by Puritan in Massachusetts, a place where the author was born and dies. Dickinson highlights the Puritan fierce rules which lead to female’s total submission.